PENGEMBANGAN KEMAMPUAN BAHASA ANAK MELALUI PENGGUNAAN MEDIA KARTU HURUF DI TK TABITHA 1 KELURAHAN BENTENG, KECAMATAN NUSANIWE, KOTA AMBON (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to determine the improvement of letter recognition skills using letter card media in children at Tabitha 1 Kindergarten, Benteng Village, Nusaniwe District, Ambon City. The study addresses the problem that children's language abilities through letter card media still need improvement, as children showed less interaction with peers, were reluctant to share, and had not fully recognized letters. The research employed Classroom Action Research (CAR) methodology conducted over two cycles with 13 children aged 5-6 years as subjects. Data collection techniques included observation, interviews, evaluation, and documentation. Results showed significant improvement in letter recognition abilities: initial condition reached 60% (8 children), Cycle I showed 60% (8 children) still underdeveloped according to expectations (BSH), necessitating continuation to Cycle II. The second cycle achieved success with 80% (11 children) developing very well (BSB) in letter recognition skills. This indicates that children at Tabitha 1 Kindergarten Ambon have achieved the expected letter recognition abilities. The learning process to improve letter recognition skills using letter card media was deemed successful, demonstrating that letter card media effectively enhances children's language development in early childhood education settings through an engaging and interactive approach.